(untitled) (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2018)
With the transformations passed in technology and the urban progress (that brought a loss is the living conditions of the population), a new mode of teaching started to highlight itself: Distance Learning. I had a great boost, especially, in the past decades, turning a worldwide trend.